The Competitive Advantage of Quality Rubber Production Network - Ittichinbanchon, Nontaya (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The research aimed to study and construct a quality rubber production network model. The study employed the participatory action research (PAR) method involving focus group discussions. and using in-depth interviews and observation techniques for data collection. Data analysis and synthesis used the inductive method. The study had three phases. The first phase was desigred to investigate the state of events and rubber production in Pusing District. The second phase was intended to study the competitive advantage for a quality rubber production network. The third phases included presentation of a competitive advantage for a quality rubber products network model. The research findings were as follows: the current stage of the rubber farmers network lacked development. collaboration and awareness: environmental aspect potential exists for constructing a competitive advantage for a quality rubber production network in the study area: and the need of finding a collaborative leader to promote regulations leading to a competitive advantage for a quality rubber production network. such as a rubber center, acting, communication, and collaboration activities. Finally, there were five mechanism aspects in management: personnel. production. marketing.financial and accounting for the continuation of the evaluation.